3D Copper Circuits: Form‐Factor Free 3D Copper Circuits by Surface‐Conformal Direct Printing and Laser Writing (Adv. Funct. Mater. 45/2020). (4th November 2020) - Jo, Yejin; Park, Hye Jin; Kim, Young‐Bin; Lee, Sun Sook; Lee, Su Yeon; Kim, Sun‐Kyung; Choi, Youngmin; Jeong, Sunho
Abstract : In article number 2004659, Sun‐Kyung Kim, Youngmin Choi, Sunho Jeong, and co‐workers propose multi‐dimensional particles that allow for deep penetration of incident photons in the surface‐conformal laser writing process. Highly conductive 3D Cu features for form‐factor free electrical circuits are created simply via successive 3D printing and laser writing processes.